An examination of the individual, contextual and situational supports factors on professional judgement of tax officers / Nurliyana Khalid - Khalid, Nurliyana (2020)
This study examines the effects of individual, contextual and situational supports factors on the tax professional judgement of tax officers. In order to provide a holistic view on tax professional judgement, this study is designed into two sub-studies denoted as Study A and Study B. Both studies utilize Partial Least Squares (PLS) of Structural Equation Modelling for data analyses. For Study A, an experimental approach is employed to a total of 176 tax officers of Inland Revenue Board of Malaysia (IRBM). The results reveal that scepticism is significant in influencing tax professional judgement either in its direct or indirect capacity, while there are no significant differences between tax auditors and tax investigators’ professional judgement. The results of Study A also demonstrate that contextual factor (client’s fraud indicators intensity) mediates the relationship between scepticism and tax professional judgement. Moreover, the interaction analysis points out that the client’s internal control significantly interacts the relationships between scepticism, client’s fraud indicators intensity and the tax professional judgement. Study B adopts a survey method with a total of 145 tax officers. This study examines the influence of antecedent factors on tax professional judgement reveals that individual factor (scepticism), contextual factor (client’s fraud indicators intensity) and situational supports significantly influence tax professional judgement. Competencies, however, is found as not significant in influencing tax professional judgement. Also, it provides further evidence that shows the existence of mediation effect of client’s fraud indicators intensity on the relationship between competencies, scepticism and situational supports factors on tax professional judgement. In overall, both studies recognize that client’s fraud indicators intensity is a critical element in improving tax officers in making tax professional judgement. Both studies suggest that individual factor (scepticism), contextual factors (client’s internal control, client’s financial pressure and client’s fraud indicators intensity), and situational supports factors affect tax professional judgement significantly in some direct and indirect context. The current research provides significant contributions to the existing body of knowledge in the tax fraud risk area by substantiating the underlying theoretical foundations and extending the fraud risk judgement framework in tax profession. In addition, the findings from this research are deemed to be useful to those in the tax audit and investigation fields in providing additional guidelines in developing and enhancing tax fraud risk assessment programs and training to improve better quality of tax professional judgement.